Analisis Penerapan Model Pembelajaran Flipped Classroom untuk Siswa Sekolah Dasar - Revita Salsabila; Wulan Ajeng Lestari; Nisa Hamidah; Ellyati Ellyati; Ani Hanipah (Wahana Didaktika : Jurnal Ilmu Kependidikan, 2021)
The development affects the characteristics of the learning process, especially when it comes to the use of technology. Technology is used as a tool to facilitate the learning process in hopes of creating more meaningful learning experiences for learners. The use of the technology depends on the selected learning model. One of the learning models that need the use of technology, flipped classroom. Flipped classroom learning models focus on student-centered teaching. These learning models are still rarely implemented in elementary schools. Hence, it aims to analyze the application of the flipped classroom learning model for elementary school students. The study used the literature review methods with a type of descriptive analysis study. The research subject is aÃ‚Â student of elementary school. Data sources are obtained from scientific journals, books, and other sources that contain the results of studies of various parties relevant to the topic of the study. As for data analysis techniques using interactive models. As a result of this study, 1) flipped classroom learning models would be more suitable for elementary school students; 2) flipped classroom learning styles are varied; and 3) the application of the flipped classroom learning model supports students to access 21st-century abilities.